1999
DOI: 10.1080/07929978.1999.10676756
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dna Polymorphism and Gynodioecy in a Natural Population of Rosmarinus Officinalis L.

Abstract: Mitochondrial genome variability was studied in a gynodioecious population of Rosmarinus officina/is L. Analysis of mitochondrial DNA organization using Southem hybridization with probes for mitochondrial genes coxll, cob, and atpA revealed a high level of mitochondrial polymorphism; 11 mitotypes were detected in a total of 27 individuals studied. One mitotype was particularly common among male fertile individuals. The remaining mitotypes were found in only one or two individuals, generally male sterile. Polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The eventual occurrence of gynodioecy in R. officinalis has been proposed as a mechanism to prevent selfing. However, the genetic determination of gynodioecy in R. officinalis is unclear and may include at least the implication of mitochondrial genes and environmental variables, as the proportion of gynodioecious versus hermaphrodite flowers in R. officinalis varies between individuals and time (Ubera‐Jiménez & Hidalgo‐Fernández, ; Hidalgo‐Fernández et al ., ; personal observation of the authors). This will not completely exclude geitonogamy or biparental inbreeding and thus cannot be considered a major driver of within‐population genetic diversity levels.…”
Section: Discussionmentioning
confidence: 92%
“…The eventual occurrence of gynodioecy in R. officinalis has been proposed as a mechanism to prevent selfing. However, the genetic determination of gynodioecy in R. officinalis is unclear and may include at least the implication of mitochondrial genes and environmental variables, as the proportion of gynodioecious versus hermaphrodite flowers in R. officinalis varies between individuals and time (Ubera‐Jiménez & Hidalgo‐Fernández, ; Hidalgo‐Fernández et al ., ; personal observation of the authors). This will not completely exclude geitonogamy or biparental inbreeding and thus cannot be considered a major driver of within‐population genetic diversity levels.…”
Section: Discussionmentioning
confidence: 92%
“…Within individual instability in male-sterility may be the result of geneticallycontrolled gender variation in interaction with the environment (Wolfe & Shmida 1997;McCauley& Bailey 2009;Harkess & Leebens-Mack 2016). On the one hand, Hidalgo-Fernández et al (1999) found that rosemary plants with some proportion of male-sterile flowers had higher mitochondrial genome variability than plants with all flowers hermaphrodite, suggesting some kind of genetic control as occurs in other Lamiaceae (Belhassen et al 1991). But on the other hand, the strong and persistent negative effect of altitude on the proportion of male-sterile flowers we found in our study is coherent with the finding that warmer temperatures favour the expression of female flowers (Koelewijn & Van Damm 1996), and point more towards an abnormal development of flowers (Richards 1997, pp.…”
Section: Accepted Articlementioning
confidence: 99%